MENCIPTAKAN KEBIJAKAN PENDIDIKAN YANG LEBIH BAIK DI INDONESIA - Deding Ishak (PAPATUNG: Jurnal Ilmu Administrasi Publik, Pemerintahan dan Politik, 2021)
Education can only be changed by society itself. Education is a picture and image of the community itself so that if the quality of education is good, the quality of the community is also good. Therefore, it is necessary to make an educational policy that does not only focus on the theory that will be developed by students. One of the efforts in creating education policy is to involve education and politics because education today cannot be separated from politics. Various education policies launched by the minister Nadiem Makarim often receive political visits from members of the council and also several mass organizations. This affects an important role in determining education policy. The success of future generations cannot unlock today's generation and the education it receives. It can be said that politics can make education in a country better or vice versa.